Catalytic conversion of sucrose to 1,2-propanediol over alumina-supported Ni-Mo bimetallic catalysts - Sreekantan, Sreejith; Kirali, Arun Arunima Balachandran; Marimuthu, Banu (Sustainable Energy & Fuels, 2022)
Ni-Mo supported on gamma-Al2O3 catalysts were synthesized to test its catalytic activity towards sucrose to 1,2-propanediol (1,2-PDO) conversion. The catalyst system was characterized using various physicochemical methods, including XRD, BET, py-FTIR, XPS, FE-SEM, HR-TEM and ICP. The metal combination of 8%Ni-20%Mo/gamma-Al2O3 is found to be effective in producing a good yield of 1,2-propanediol (similar to 74%) under mild reaction conditions of 180 degrees C, 40 bar H-2 pressure and a run time of 4.5 h in a batch reaction. The activity of the active catalyst over various substrates such as cellulose, glucose, fructose and real-source biomass has also been investigated. XPS analysis of the active catalyst confirms the various oxidation states of the metals Ni and Mo in the active catalyst. The py-IR results show that the optimum Lewis to Bronsted acidic site ratio is responsible for the selective conversion of sucrose to 1,2-PDO. The presence of interparticle mesopores on gamma-Al2O3 helps in the high conversion of sucrose. Furthermore, the catalyst has been found reusable for four consecutive runs without any structural or morphological changes.

Ce promoted Cu/?-Al2O3 catalysts for the enhanced selectivity of 1,2-pro-panediol from catalytic hydrogenolysis of glucose - Kirali, Arun Arunima Balachandran; Sreekantan, Sreejith; Marimuthu, Banu (Catalysis Communications, 2022)
Ce promoted Cu/gamma-Al2O3 catalysts were prepared with varying amounts of Cu (x = 0-10 wt%) and Ce (y = 0-15 wt%). The prepared catalysts were characterized and tested for the conversion of aqueous glucose (5 wt%) to 1,2propanediol in a batch reactor. 10%Ce-8%Cu/gamma-Al2O3 & nbsp;showed the complete conversion of glucose with 62.7% selectivity of 1,2-propanediol and total glycols (1,2-propanediol, ethylene glycol & 1,2-butanediol) of 81% at milder reaction conditions. Cu facilitated the hydrogenation activity and Ce loading optimize the acid/base sites of Cu/gamma-Al2O3 which obtain high selectivity of 1, 2-propanediol. Catalyst reusability is reported.
Keywords: 2-Propanediol; 1; Cu-Ce catalyst; ethylene glycol; Gamma alumina; Glucose hydrogenolysis

Ligand-free one-pot synthesis of Ru/W18O49 self-assembled hierarchical coral-like nanostructures for selective conversion of glucose into glycols - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Kirali, Arun Arunima Balachandran; Marimuthu, Banu; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2023)
In this study, we report a simple inorganic route for the synthesis of Ru/W18O49 self-assembled coral-like nanostructures, with the following advantages: It is one step and requires no surfactant or stabilizing agent; Ru loading is easily tuned, and the as-synthesized nanomaterials can be used as a catalyst without any further processing. The preliminary investigations of the catalytic performance of these as-synthesized Ru/W18O49 nanomaterials appear quite promising for converting glucose to glycols. The total glycol selectivity of 82.6% with 100% conversion of glucose was obtained over 0.03 wt % Ru loading on tungsten nanostructures, which turns out to be the lowest Ru loading% on support reported to date to achieve the highest total glycol selectivity among the previously reported catalyst based on Ru-nano/composite materials. Additionally, preliminary results show that the concentration of Ru on W18O49 significantly affects the selectivity of the glycol production. Thus, our methodology will open up a wide range of opportunities regarding the choice of metals, stoichiometric/nonstoichiometric WOx (x=1-3) as support, and the viability of further catalytic manipulations. A probable catalytic mechanism for this catalytic process is also proposed.
Keywords: glycols; Nanostructure; One-pot synthesis; ruthenium (Ru); selective conversion of glucose; tungsten oxide (W18O49)

Enhanced catalytic conversion of disaccharides to propylene glycol using metal-supported graphitic carbon nitride - Kirali, Arun Arunima Balachandran; Narayanan, Hariprasad; Viswanathan, Balasubramanian; Yadav, Parmeshwar; Marimuthu, Banu (Energy and Fuels, 2024)
Propylene glycol (or) 1,2-propanediol (1,2-PD) is an important polyol widely used for pharmaceuticals, polyester resins, paints, cosmetics, antifreeze, etc. Sucrose has emerged as a promising feedstock to produce 1,2-PD, as indicated by recent research findings. Graphitic carbon nitride (g-C3N4/gCN) was synthesized by using different crucibles. Ni-Mo was loaded on different g-C3N4 supports via the wetness impregnation method for sucrose hydrogenolysis. Effects of different g-C3N4 supports were studied. Catalysts with varying Ni (x = 0-8 wt %) and Mo (y = 0-15 wt %) contents were characterized using XRD, BET, XPS, FE-SEM, Py-FTIR, HR-TEM, TPD (CO2)and Raman spectroscopy. An attempt was made on sucrose conversion into 1,2-PD using a Ni-Mo/g-C3N4 catalyst. The catalyst containing 8% Ni and 10% Mo on Gr-gCN exhibited the best performance, achieving complete sucrose conversion with a 76% yield of 1,2-PD under mild reaction conditions. The presence of highly dispersed nanoparticles and the nature of graphitic carbon nitride help improve the reactions' yield by allowing reactions at lower temperatures, reducing the occurrence of side reactions, and increasing recycling rates. A straightforward approach to material preparation, coupled with the exceptional dispersion of metal nanoparticles, paves the way for a novel platform for biomass conversion.

One-pot catalytic conversion of sucrose to 1,2-propanediol over titania supported Ni-Ce metal catalyst under milder reaction conditions - Sreekantan, Sreejith; Sreedharan, Sarath; Kirali, Arun Arunima Balachandran; Yadav, Parmeshwar; Marimuthu, Banu (Biomass Conversion and Biorefinery, 2024)
The increased energy demand and decreasing fossil resources have driven the research community to look into a sustainable, green process to meet the energy demands. India being one of the top producers of sugarcane derived sucrose, and conversion of surplus sucrose to value chemicals is always an advantage. 5%Ni-15%Ce/TiO2 catalyst is found to produce high yield of 1,2-PDO (similar to 74%) under very mild reaction condition of 180 degrees C, 30 bar H-2 for 3-h reaction time. The characterization of the catalyst by using various physicochemical methods indicates the synergy between Ni-Ce bimetal which enhances the selective production of glycol. The low temperature and pressure requirement and the advantage of being the one-pot process will always attract the future scope of commercialization.
Keywords: Glycol; Low pressure; Low temperature; Ni-Ce catalyst; Sucrose; titania